The INFLUENCE OF ORGANIZATIONAL CAPABILITIES ON THE FINANCIAL PERFORMANCE OF INSURANCE IN KENYA - Owuor, Ezekiel Otieno (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this study was to establish the influence of organizational capabilities on the financial performance of insurance in Kenya. Methodology: The paper employed desktop methodology, which involved review of existing literature relating to the study topic. The design involves a review of existing studies relating to the research topic. Results: Based on past literature the study concluded that government ownership had a negative relationship with asset quality, earnings quality and management efficiency indicating laxity in prudent credit management practices and also inefficiency of operations and poor returns. Institutional ownership on the other hand showed a positive relationship with most of the parameters with an exception of some commercial banks. This means that governance capability enhances organizational performance. Further, lack of knowledge of financial management leads organizations to serious problems regarding financial performances. The study found out that financial innovations influence organizational financial performance a very great extent. The results revealed that the relationship between innovation capabilities; innovation efforts and firm performance are significant and strong. Human resource capability is valuable, rare, irreplaceable, and difficult to imitate; therefore, it is crucial for creating sustainable competitive advantages. Human resource capability can be appropriately used to improve the performance of an organization. The study findings further showed that government does not have a role in shaping the entrepreneurial spirit, because the entrepreneurial spirit has been formed in their environment and such acts are hereditary. In addition, the study concluded that market share has a significant effect on Annual Profit, Return on Assets and Net Profit Margin. It means that greater the market share, greater the profitability of the firm. Unique contribution to theory, practice and policy: Based on the findings, the study recommended that insurance firms should capitalize on their capabilities and this will enhance their financial performance. The study further recommended the need for insurance firms to adopt effective financial management practices and this will lead to improved financial performance. As such, insurance firms should adopt the use of modern technology and this will improve their performance. Insurance firms should develop a culture of adhering to the guiding rules and regulations as stipulated in the regulations Act.